The new oncogene transmembrane protein 60 is a potential therapeutic target in glioma - Yang, Fengdong; Zhang, Xuezhi; Wang, Xinzhuang; Xue, Yake; Liu, Xianzhi (Frontiers in Genetics, 2023)
Glioma is a malignant tumor with a high fatality rate, originating in the central nervous system. Even after standard treatment, the prognosis remains unsatisfactory, probably due to the lack of effective therapeutic targets. Thus, it is necessary to explore the molecular and clinical characteristics of newly identified oncogenes, such as transmembrane protein 60 (TMEM60), to develop effective treating options for glioma. We used bioinformatic methods and basic experiments to verify the expression of TMEM60 in gliomas and its relationship with 1p and 19q (1p19q) status, isocitrate dehydrogenase (IDH) status, patient prognosis, and immune cell infiltration using public databases and clinical samples. In addition, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to detect co-expressed genes. Finally, we inhibited the expression of TMEM60 to observe the proliferation and activity of glioma LN229 cells. TMEM60 was significantly upregulated in glioma compared with that in normal brain tissue at the mRNA level. In the subgroups of World Health Organization grade, IDH status, 1p19q status, and IDH status combined with 1p19q status, the expression of TMEM60 increased, and the prognosis of glioma patients worsened. In the TMEM60 high expression group, infiltration of immune cells and stromal cells in the tumor microenvironment increased, tumor purity decreased, and immune cells and pathways were activated. The immune cells mainly included regulatory T cells, gamma delta T cells, macrophages M0, neutrophils, and CD8+ T-cells. GO and KEGG analyses showed that TMEM60 might participate in the malignant behavior of tumors through processes involving the cell cycle, proteasome, DNA replication, and mismatch repair. Finally, we found that TMEM60 silencing weakened the viability, proliferation, and clonogenic ability of glioma LN229 cells. This is the first report on the abnormally high expression of TMEM60 in glioma and its related clinical features, such as tumor microenvironment, immune response, tumor heterogeneity, and patient prognosis. We also found that TMEM60 silencing weakened the proliferation and clonogenic ability of glioma LN229 cells. Thus, the new oncogene TMEM60 might be an effective therapeutic target for the clinical treatment of glioma.